Radiation Protection Knowledge, Attitude and Practice (RP-KAP) as Predictors of Job Stress Among Radiation Workers in Tehran Province, Iran - Alavi, S. Shohreh (Iran Red Crescent Med J, 2016)
BACKGROUND: In recent years, much attention has been paid to occupational stress, but relatively little or no research has been conducted on the influence of knowledge, attitude, and practice of radiation protection (RP-KAP) on job stress among radiation workers OBJECTIVES: This study aims to assess job stress among health care workers in Iran who are occupationally exposed to radiation in order to determine the effects of KAP on self-protection against radiation on their job stress. MATERIALS AND METHODS: The population in this descriptive cross-sectional study comprised 670 healthcare workers, including 428 staff with a degree in radiology and 242 other medical personnel who were working in 16 hospitals affiliated with Tehran University of Medical Sciences (TUMS) in Tehran, Iran. The census method was used to sample the workers. In total, 264 staff with a degree in radiology and 149 other medical personnel completed the job content questionnaire (JCQ) and the RP-KAP questionnaire from May to November 2014. RESULTS: The prevalence rate of job stress was 22.5% based on calculation formulas and possible scores on the JCQ. Sex, RP-knowledge, attitude, practice, and in-service training predicted 41.8% of the variance in job stress. According to the results of the binary logistic regression, workers with higher scores on knowledge (OR = 0.82, 95% CI: 0.75 - 0.90), attitude (OR = 0.71, 95% CI: 0.63 - 0.82), and practice (OR = 0.78, 95% CI: 0.72 - 0.86) and those who had participated in training programs had significantly lower rates of job stress (OR = 0.51, 95% CI: 0.28 - 0.93). CONCLUSIONS: The effects of RP knowledge, attitude, and practice on job stress were significant. In order to reduce job stress in radiation environments, ongoing training programs related to self-care and protection principles are recommended.